Analisis Reduplikasi pada Karangan Narasi Siswa Kelas X Sma Negeri 1 Karangpandan - Afriliana, Ayu Linda, Drs.Yakub Nasucha,M.Hum (2017)
This study aims to (1) describe the process of reduplication in narrative essay class X SMA Negeri 1 Karangpandan and (2) Describe the meaning of the narrative essay reduplications in class X SMA Negeri 1 Karangpandan. This study used descriptive qualitative method. Sources of data obtained from a narrative essay class X SMA Negeri 1 Karangpandan. Data analysis technique used is the decisive element sorting technique or techniques PUP.The results of this study were (1) The process of reduplication in Narrative Narrative Class X SMAN 1 Karangpandan found four, namely (a) the repetition of the whole, (b) repetition throughout the basic shape without change phonemes and not in combination with the process of affixing affixes, ( c) repetition is repetition of some of the most basic form, in other words, the basic shape is not repeated in full, repetition combined with affixes affixing process, and (d) repetition with a change of phonemes, which said that the repetition e-include this group is actually very little. The majority of the use of reduplication used by students of Class X SMAN 1 Karangpandan is repetition over with the intention of delivering meaning under the age of students. (2) The meaning reduplications on Narrative Writing Class X SMAN 1 Karangpandan is though, a lot, actually, resembling, repeatedly and have fun. But more dominated by the intent of delivering meaning of number and amount of an imagination to convey the students.Keyword : Reduplication, Narrative Essay Grade X SMAN 1 Karangpandan.